The Relevance of The Principles of Muamalah in Addressing Contemporary Disruptions in International Trade - Rayhan Nur Fikri; Muhammad Alif Shafwan; Darriel Fadhilah; Muhammad Emir Fathan Alhafiz (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the relevance of muamalah principles in addressing contemporary disruptions in international trade through a non empirical qualitative approach based on conceptual and theoretical analysis. The research employs an extensive literature review of scholarly publications in Islamic economics, international trade, business ethics, and digital commerce. Data were analyzed using qualitative content analysis and thematic interpretation involving concept extraction, comparative evaluation, thematic categorization, and theoretical synthesis. The findings indicate that contemporary trade disruptions have generated significant governance challenges related to market inequality, contractual legitimacy, accountability, technological transformation, and sustainability. The study demonstrates that the principles of muamalah possess substantial explanatory and normative relevance for responding to these challenges through ethical governance mechanisms rooted in justice, consensual transactions, responsibility, and truthfulness. The analysis further reveals that muamalah can evolve beyond a transactional doctrine into a comprehensive framework capable of guiding digital trade governance, institutional adaptation, technological oversight, and sustainable commercial development. The proposed framework integrates ethical values with emerging global trade realities and contributes to the development of a more resilient, transparent, and sustainable international trading system. These findings reinforce the continuing significance of Islamic commercial ethics within the evolving architecture of global economic governance.